Heritage of coal mining: experience of inventory of architectural and landscape cultural heritage in Arroio dos Ratos (RS) - Stocker Júnior, Jorge Luís (2022)
This paper presents the partial results obtained in the experience of registering the architectural and landscape cultural heritage in the municipality of Arroio dos Ratos, in the Carboniferous Region of Rio Grande do Sul. The study was developed under the project Memories of Arroio dos Ratos, financed by the Sistema Pró-Cultura RS / FAC, and resulted in the inventory of 39 architectural and landscape cultural references. Using an adaptation of the methodology named Sistema de Rastreamento Cultural IPHAE/RS, the cultural assets were inventoried between the different historical periods identified: Mining Beginnings (1855-1888), End of the 19th Century (1878-1900), Beginning of the Century XX (1900-1940), Estado Novo/CADEM (1940-1964) and Emancipation (1964-present). The Inventory allows the mobilization of the community and public authorities for the preservation of the cultural references and their symbolic meanings.